Lichen-Associated Fungal Community in Hypogymnia hypotrypa (Parmeliaceae, Ascomycota) Affected by Geographic Distribution and Altitude - Wang, Yanyan; Zheng, Yong; Wang, Xinyu; Wei, Xinli; Wei, Jiangchun (Frontiers in Microbiology, 2016)
Lichen-associated fungal species have already been investigated in almost all the main growth forms of lichens, however whether or not they are homogeneous and constant within each lichen species are still inconclusive. Moreover, the related ecological factors to affect and structure the fungal composition have been poorly studied. In order to answer these questions, we took Hypogymnia hypotrypa as a model to study the relationship between the lichen-associated fungal composition and two ecological factors, i.e. site and altitude, using the method of IlluminaMiSeq sequencing. Four different sites and two levels of altitude were included in this study, and the effects of site and altitude on fungal community composition were assessed at three levels, i.e. OTU, class and phylum. The results showed that a total of 50 operational taxonomic units (OTUs) were identified and distributed in 4 phyla, 13 classes and 20 orders. The lichen-associated fungal composition within H. hypotrypa were significantly affected by both site and altitude at OTU and class levels, while at the phylum level, it was only affected by altitude. While the lichen associated fungal communities were reported to be similar with endophytic fungi of the moss, our results indicated the opposite results in some degree. But whether there exist specific OTUs within this lichen species corresponding to different sites and altitudes is still open. More lichen species and ecological factors would be taken into the integrated analyses to address these knowledge gaps in the near future.